Disease of poultry - Barnes, H. John; Saif, Y. M. (Blackwell Publishing, 2008)
Now in its Twelfth Edition, Diseases of Poultry continues its tradition of excellence as the definitive reference of poultry disease. Following the same user-friendly format, the book has been thoroughly updated to reflect the most current knowledge of avian pathology, including new coverage of genetic resistance to disease